Organisational Support for Job Satisfaction of Academics in A Virtual Contexts at a Selected Institution of Higher Learning in the Eastern Cape Province of South Africa - Mefi , Nteboheng Patricia; Asoba, Samson Nambei (Journal of Ecohumanism, 2025)
With increased virtualization of high education given the Fourth Industrial Revolution (4IR) as well as in response to the Covid-19 pandemic concern has been raised over the implication of this on the job satisfaction of academics. The aim of this study was to determine the effectiveness of the support given to academics in ensuring job satisfaction of the academics working online. A quantitative methodology which was based on the collection of data using a questionnaire given to academics was adopted. The results indicated that sixty percent (60.4%) of the respondents had received some support by university management. Most support for the virtual environment was provided through workshops and training. However, the support given was not consistent with the other finding that eighty six percent (86%) of the academics had indicated that the major factor affecting their job satisfaction was connectivity and lack of cooperation of students (42.6%). It is encouraged that HEIs should strengthen their relationships and cooperation with supportive institutions for virtualisation such as ESKOM as well as the private and public community.